Design and optimization of cobalt-encapsulating vertical graphene nano-hills for hydrogen evolution reaction. Issue 28 (5th July 2019) - Roy, Sanjib Baran; Jerng, Sahng-Kyoon; Akbar, Kamran; Jeon, Jae Ho; Truong, Linh; Chun, Seung-Hyun; Noh, Min Jong; Lee, Juho; Kim, Yong-Hoon
Abstract : Cobalt-encapsulating vertical graphene nano-hills exhibit high hydrogen evolution reaction activity because of the synergistic effects of curvature and doping. Abstract : In spite of its great potential for sustainable water splitting technology, many challenges remain for the development of effective graphene-based hydrogen evolution reaction (HER) electrocatalysts. Based on mutually corroborating growth, electrochemical measurements, and density functional theory (DFT) calculations, we herein develop the HER-active vertical graphene nano-hills (VGNHs) on Co thin films such that Co atoms are introduced into the VGNH tip region. The HER activity exhibits a volcano-shaped curve with respect to the encapsulated Co density, and the best performance achieved at the nominal Co substrate thickness of 1 nm is characterized by the low onset potential, overpotential, and Tafel slope in acidic electrolyte. Especially, with this low-cost yet structurally and chemically stable Co-seeded VGNH catalyst, a record-level mass activity is achieved. The emergence of the HER activity from the combination of originally HER-inactive VGNHs and Co thin films is clarified by DFT calculations, which identifies the synergistic effects of the nanoscale curvature at the VGNH tip and the charge-transfer doping by encapsulated Co atoms.